Evaluation of Perfusion Quantification Methods with Ultrasound Contrast Agents in a Machine-Perfused Pig Liver - Averkiou, Michalakis; Keravnou, Christina P.; Izamis, Maria Louisa; Leen, Edward (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose To evaluate dynamic contrast-enhanced ultrasound (DCEUS) as a tool for measuring blood flow in the macro- and microcirculation of an ex-vivo machine-perfused pig liver and to confirm the ability of DCEUS to accurately detect induced flow rate changes so that it could then be used clinically for monitoring flow changes in liver tumors.Materials and Methods Bolus injections of contrast agents in the hepatic artery (HA) and portal vein (PV) were administered to 3 machine-perfused pig livers. Flow changes were induced by the pump of the machine perfusion system. The induced flow rates were of clinical relevance (150 – 400 ml/min for HA and 400 – 1400 ml/min for PV). Quantification parameters from time-intensity curves [rise time (RT), mean transit time (MTT), area under the curve (AUC) and peak intensity (PI)] were extracted in order to evaluate whether the induced flow changes were reflected in these parameters.Results A linear relationship between the image intensity and the microbubble concentration was confirmed first, while time parameters (RT and MMT) were found to be independent of concentration. The induced flow changes which propagated from the larger vessels to the parenchyma were reflected in the quantification parameters. Specifically, RT, MTT and AUC correlated with flow rate changes.Conclusion Machine-perfused pig liver is an excellent test bed for DCEUS quantification approaches for the study of the hepatic vascular networks. DCEUS quantification parameters (RT, MTT, and AUC) can measure relative flow changes of about 20 % and above in the liver vasculature. DCEUS quantification is a promising tool for real-time monitoring of the vascular network of tumors.
Keywords: DCEUS quantification; ex-vivo pig liver; machine perfusion; liver flow rate; therapy monitoring